Structural and morphological properties of pristine and Zn doped CdO nanoparticles for thermoelectric applications. (2022) - Madan, Rahul; Kumar, Vikas; Mohan, Devendra
Abstract: The Chemical Precipitation method was adopted to synthesize Pristine CdO and Zn doped CdO Nanoparticles with 2% Zn Concentration for thermoelectric applications. The crystal structure of the synthesized nanoparticles was investigated by X-ray diffraction at room temperature. Rietveld Refinement technique was used to evaluate the detailed structural parameters from X-Ray Diffraction data which confirmed the face centred cubic structure of the prepared material with space group Fm 3 - m. The FE-SEM images confirmed the presence of nanoparticles with irregular shapes. EDX analysis confirmed the presence of constituent elements in the prepared materials. Since Nanostructuring results in increment in power factor and reduction in thermal conductivity so the figure of merit is expected to increase. Thus the prepared material is efficient for thermoelectric applications.